Youth Violence Sources and solutions in South Africa - Ward, Cathy; Dawes, Andrew (UCT Press, 2012)
Youth violence: sources and solutions in South Africa thoroughly and carefully reviews the evidence for risk and protective factors that influence the likelihood of young people acting aggressively. Layers of understanding are built by viewing the problem from a multitude of perspectives, including the current situation in which South African youth are growing up, perspectives from developmental psychology, the influences of race, class and gender, and of the media. The book examines the evidence for effective interventions in the contexts of young people's lives - their homes, their schools, their leisure activities, with gangs, in the criminal justice system, in cities and neighbourhoods, and with sexual offenders. In doing so, thoughtful suggestions are made for keeping an evidence-based perspective while (necessarily) adapting interventions for developing world contexts, such as South Africa.